Zagrożenie życia narodu jako przesłanka wstępna derogacji zobowiązań w dziedzinie praw człowieka - Jasudowicz, Tadeusz (Studia Prawa Publicznego, 2020)
To determine the fate of human rights in extreme situations, the treaties contain a mechanism for derogating from obligations, i.e. derogations from their enforceability in such exceptional situations. The initial and fundamental criterion under which derogation steps are admissible is the existence of an exceptional public emergency that threatens the life of the nation, as referred to in Article 4(1) of the International Covenant on Civil and Political Rights and Article 15(1) of the European Charter of Human Rights, and about which Professor Anna Michalska wrote so competently in 1997. Neither the constitutions of modern states nor their practice of introducing states of emergency are helpful in defining this criterion more precisely; most often, they do not use it at all. Unfortunately, it is not to be found in Chapter XI of the Polish Constitution “States of Emergency”, nor in the laws of 2002 regulating these states. In the practice of the treaty monitoring bodies (Human Rights Committee in the ICCPR system; the European Commission and the Court of Human Rights in the ECHR system), we do not find incontestable nor indisputable indications. The concept of the “nation” is referred to society as a whole and is to be associated with its physical survival. In the author’s opinion, this is not the correct approach, as it is and must be about a “living nation”, a nation effectively exercising its rights. The enslavement of a nation, its subjugation, elimination of opportunities for its self-determination – far from its extermination – can unquestionably meet the requirements of the criterion of a threat to the life of the nation. The study of constitutional law (the nation-sovereign) and international law (the principle and right to self-determination of the nation) unequivocally confirms this thesis.